2013
DOI: 10.1149/2.088306jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Formulations Based on Dinitrile Solvents for High Voltage Li-Ion Batteries

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
102
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 28 publications
1
102
0
4
Order By: Relevance
“…In practical applications of lithium-ion batteries, the selection of the electrode material is critical, particularly when using high surface area nanomaterials. 15 Enhanced chemical stability against electrolyte oxidation and reduction, high ionic conductivity, high boiling points, and low melting points are required, as well as the ability to solvate a wide range of lithium salts such as LiPF 6 , LiBF 4 or LiClO 4 , [16][17][18][19][20][21] in aprotic and organic solvents such as ethylene carbonate (EC), propylene carbonate (PC), their mixtures, and ionic liquids. The decomposition mechanism of organic solvent and subsequent formation of SEI films near the graphite anode is a major research topic in lithium ion batteries from theoretical [22][23][24][25][26][27][28][29][30] and experimental [31][32][33][34][35][36][37][38][39] standpoints, and one of the least understood.…”
mentioning
confidence: 99%
“…In practical applications of lithium-ion batteries, the selection of the electrode material is critical, particularly when using high surface area nanomaterials. 15 Enhanced chemical stability against electrolyte oxidation and reduction, high ionic conductivity, high boiling points, and low melting points are required, as well as the ability to solvate a wide range of lithium salts such as LiPF 6 , LiBF 4 or LiClO 4 , [16][17][18][19][20][21] in aprotic and organic solvents such as ethylene carbonate (EC), propylene carbonate (PC), their mixtures, and ionic liquids. The decomposition mechanism of organic solvent and subsequent formation of SEI films near the graphite anode is a major research topic in lithium ion batteries from theoretical [22][23][24][25][26][27][28][29][30] and experimental [31][32][33][34][35][36][37][38][39] standpoints, and one of the least understood.…”
mentioning
confidence: 99%
“…In addition, one of the main issues with high voltage batteries is the instability of common aprotic electrolytes at voltage above 4.5 V. 6,7 The stability of the electrolyte/cathode interphase is related to the chemistry of electrolyte solvents and salts and also to the chemistry of the components of the cathode.…”
mentioning
confidence: 99%
“…5 The possibility of using adiponitrile and glutaronitrile as electrolyte solvents was investigated thoroughly.…”
mentioning
confidence: 99%
“…Based on the results of reference 3, it is possible that nitriles as electrolyte additives can be potential candidates to improve cycle life because results in the literature showed that EC:DMC mixed with nitrile co-solvents has high electrochemical stability up to around 5.0 V and starts to be oxidized at around 5.5 V vs. Li/Li + , while pure EC:DMC starts to be oxidized suddenly at around 4.5 V. [4][5][6][7] Nigahara et al reported that 1.0 M LiBF 4 EC:DMC:sebaconitrile (25:25:50 by vol %) showed the best electrochemical compatibility with positive electrode materials such as LiMn 2 O 4 and LiCoPO 4 in experiments involving the nitriles: glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, sebaconitrile and dodecanedinitrile at high voltage. 4 Duncan et al showed that dinitriles with shorter carbon chain length between nitrile groups gave higher capacities in Li-ion cells than dinitriles with longer carbon chain between nitrile groups because the shorter dinitriles showed higher ionic conductivity than the longer dinitriles.…”
mentioning
confidence: 99%
See 1 more Smart Citation